The flat-field method based on rotated images for FY-3E/X-EUVI - Ding, Guangxing; Wu, Kun; He, Lingping; Chen, Bo; Liu, Fei (Frontiers in Physics, 2022)
An algorithm to calculate the flat field coefficient based on series of rotated images captured by the solar X-ray and Extreme Ultraviolet Imager (X-EUVI) onboard Fengyun-3E satellite is proposed in this paper. The method includes determination of the solar disk centers and radiuses, calculation of the rotation angles, coordinate transformation to expand the solar disk into rectangles, and derivation of the flat matrix using KLL algorithm. The accuracy of determination of the solar disk center and radius tested by Hough gradient method and the least square method are at sub-pixel, and the precision of the calculated rotation angle based on the log-polar transform is less than 0.025°. Since the X-EUVI rotates relative to the Sun in real time, multiple rotating images can be obtained and used for flat-field calibration at any time and the tested accuracy is estimated at (0.79 ~ 3.42) %. This flat field method will provide reference and support for solar image processing and research.